Ways of Improving the Training of Interns Pediatricians and General Practitioners - Family Physicians in «Pediatrics» Discipline - S.A. Mokiia-Serbina; T.V. Lytvynova; V.V. Chechel (Zaslavsky O.Yu., 2015)
Graduates of medical schools having sufficient theoretical and practical skills often have difficulty in communicating with patients - children and their parents, as well as with colleagues. Objective: improving the efficiency of the educational process in the training of interns pediatricians and general practitioners - family physicians in «Pediatrics» course. Methods of the study: theoretical analysis of gathered experience. Results and discussion. During internship at the department, there are used seminars-discussions, seminars - training conferences, seminars - round tables that allows you to work out the tactics of speech, methods of discussion, reasoning of judgments, review, assessment, analysis. Interns most of the time must participate in the examination of a sick child, discussions of the results, conversations with parents. Clinical analysis of patients should be carried out using the method of structured group discussion when each intern can express his views. Interns are involved in scientific work, speak at scientific conferences. The department created a series of ambulatory pediatrics, -during which the intern talks to a child, his parents and he must to conciliate them, to inspire confidence and to prove himself as a specialist. During this course, special attention is paid to the psychological component of medical trai-ning. Clas-ses are conducted by assistant pediatrician, a graduate majoring in «Practical Psychology». Conclusions. The use of interactive teaching methods at different stages of the educational process contributes not only to improvement of theoretical activity, but also the formation in interns of professional qualities of clinical and scientific thinking, competence in the construction and development of interpersonal relations, humanism.